Food Consumption Patterns in Romania during the COVID-19 Pandemic - Diana E. Dumitras (MDPI AG, 2021)
Food consumption behavior during the COVID-19 pandemic has changed worldwide as a consequence of the restrictions imposed by law and/or due to the fear of contamination. Although some similarities are found among countries, there are still many particularities for each nation. The present study focused on Romanian consumers and their consumption behavior related to four main food categories: fruits and vegetables, meat and meat products, bread and bakery products, and milk and milk products. Frequency of buying, shopping habits, place of purchase, and concerns related to the place of purchasing food products during the COVID-19 pandemic were analyzed in comparison with the pre-COVID-19 period using descriptive statistics and inferential statistics regarding an online survey. Three types of behavior were identified as being related to the frequency of buying and to organizing a shopping list (less often, no change, more often). Two groups of consumers were identified as being related to the place of purchasing food: people with the same habits and people with new habits. Concerns related to the location of the stores and to the choice of buying directly from producers were also investigated using the ordered logistic regression. The empirical study revealed the new consumption patterns with a reflection on future trends.